PENGUKURAN USABILITAS APLIKASI LOGISTIK BERBASIS ANDROID UNTUK MENDUKUNG KINERJA LOGISTIK PROYEK KONSTRUKSI - Pramono, Dedi; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study develops an Android-based logistics monitoring system to enhance efficiency in material management for construction projects. The research method includes system requirements analysis, application development using the Kodular.io platform, and functionality testing with project stakeholders. The results show that this application optimizes material stock monitoring, speeds up request and issuance processes, and improves logistics data accuracy. Implementing this system can improve material management effectiveness and reduce project delays due to material shortages.Keywords: Logistics management, Material monitoring, Android application, Kodular.io